MANIFESTATIONS OF POWER - DISCOURSE - KNOWLEDGE MICHEL FOUCAULT AS A MODEL - Al Jabbar, Marwa Amer Abed (PT. Antis International Publisher, 2026)
Objective: This study aims to analyze Michel Foucault’s conceptualization of power, discourse, and knowledge, emphasizing his philosophical departure from traditional notions of centralized authority. Method: Using a qualitative descriptive approach through critical textual analysis of Foucault’s key works—such as Discipline and Punish and The Archaeology of Knowledge—the study explores how Foucault constructs an interdependent relationship between power and knowledge within social structures. Results: The findings reveal that Foucault reconceptualizes power as diffuse, relational, and embedded in everyday practices rather than confined to formal political hierarchies. Knowledge, in this framework, becomes both a product and an instrument of power, shaping discourse and social order. Discourse, in turn, functions as a mechanism through which power is manifested, legitimized, and reproduced across institutions. Novelty: This study contributes to philosophical scholarship by highlighting Foucault’s unique synthesis of power and knowledge as mutually constitutive forces, offering a critical framework to understand contemporary social, cultural, and epistemological dynamics beyond classical political paradigms.